The relationship of the autonomic regulation of heart rate with postural control indicators in young athletes - Nazarenko, A.S.; Mavliev, F.A. (Theory and Practice of Physical Culture, 2026)
Abstract Objective of the study is to study the features of the autonomic regulation of heart rate and postural control in young badminton athletes. Methods and structure of the study. The scientific work was conducted on the basis of the Research Institute of Physical Culture and Sports of the Volga Region State University of Physical Culture, Sports and Tourism. 16 young athletes engaged in badminton with a level of sports mastery from the second adult category to candidate for master of sports, and 26 representatives of the control group not engaged in sports were examined. Postural control was assessed using a stabiloplatform with biofeedback by means of the Romberg test (eyes-open and eyes-closed test), as well as the registration of the electrocardiogram and heart rate variability using the PowerLab installation (ADInstruments, Australia). Results and conclusions. Significant correlations were revealed between the indicators of heart rate variability and the stabilographic parameters of postural control, in particular, with the eyes closed. The athletes exhibited a higher level of the absolute power of VLF and a dominance of the sympathetic nervous system, which possibly reflects the role of centralized autonomic mechanisms in ensuring the stability of postural control. At the same time, the differences in motor activity form the features of the autonomic regulation and postural control, but the direct influence of the autonomic system on postural control may be non-obvious.